Explaining consumer inaction in boycott movements: A psychological framework of passivity during periods of social change - Akhmad Saputra Syarif; Dwi Yan Nugraha; Amya Bunga Fathiyah (Personifikasi: Jurnal Ilmu Psikologi, 2026)
Research on collective action has primarily focused on participation, while the mechanisms underlying non-participation remain less understood. This study examines why individuals remain inactive in boycott movements despite holding negative attitudes toward targeted companies, focusing on animosity toward firms associated with Israel. Using a quantitative design, data from 212 Indonesian participants were analyzed using partial least squares structural equation modeling (PLS–SEM) and artificial neural network–neural network regression (ANN–NNR). The PLS–SEM approach was employed to examine explanatory relationships leading to purchasing behavior (PB). The results indicate that several hypothesized predictors do not exhibit significant direct effects on PB, while indirect effects are partially supported through mediating mechanisms. To complement the explanatory model, ANN–NNR results identified out of sight as the most important predictor of PB, followed by boycott attitude and urge of freedom. This divergence suggests that psychological mechanisms differ between explanatory and predictive frameworks, with ANN capturing potential nonlinear relationships. Overall, the study highlights the value of integrating PLS–SEM and ANN–NNR to better understand boycott-related inaction in a non-Western context.